Erectile Dysfunction After Radical Prostatectomy: Disfunc?a?o Ere?til Apo?s Prostatectomia Radical - Barreira, João Vasco; Falcão, Gil; Parmanande, Anuraj; Fernandes, Francisco; Louro, Nuno (Gazeta Médica, 2019)
Erectile dysfunction (ED) is a well-recognized complication resulting from pelvic surgery. The demand for good post-operative quality of life has been increasingly important and ED can have a profound effect on this. The incidence of prostate cancer continues to increase; the diagnosis tends to be done at earlier stages of the disease than before, and a greater number of men will eventually be subjected to curative therapy, including radical prostatectomy (RP). The pathophysiology of ED after RP involves three major factors: neural injury, vascular injury and damage to the corporal smooth muscle. Consequently, the recovery of erectile function (EF) is dependent on the degree and reversibility of these lesions. Concurrent with the sharp advancement of surgery, also the treatment of ED has changed dramatically over the years. The concept of early penile rehabilitation after RP occurred in the 1990s. The pharmacological prophylaxis with oral agents or intracavernous as well as the use of other devices, may have an increasing role in therapeutic strategies aimed at preservation of EF postoperatively. New developments are interesting, but they require long-term study. Focusing attention on treatment of ED after RP will reveal the advantages of proposed therapies as well as a systematization of knowledge in this area and the resulting contribution to a better clinical practice.